2015
DOI: 10.1590/0100-2945-114/14
|View full text |Cite
|
Sign up to set email alerts
|

DISTRIBUIÇÃO ESPACIAL DO BICHO-FURÃO,Gymnandrosoma aurantiana (Lima, 1927)(LEPIDOPTERA: TORTRICIDAE),EM CITROS UTILIZANDO GEOESTATÍSTICA

Abstract: RESUmO -o bicho-furão, Gymnandrosoma aurantiana (lima, 1927), é uma das principais pragas da citricultura brasileira, pois os frutos atacados pelas lagartas tornam-se inviáveis para o consumo in natura e processamento industrial. objetivou-se estudar a distribuição espacial dos danos causados por G. aurantiana utilizando geoestatística. Para tanto, foi conduzido um experimento em um pomar de laranjeira-doce da variedade 'valência', enxertado sobre limoeiro 'Cravo', localizado em Taquaritinga-SP, Brasil. a área… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
4
0
2
Order By: Relevance
“…These authors concluded that almost 100% of the variable obtained better adaptation to the spherical model, in comparison to the other models tested. A similar result was also found by Carvalho et al (2015). These authors found that the spherical model was the one that better adjusted the infestation of Gymnandrosoma aurantiana larvae (Lima, 1927) (Lepidoptera: Tortricidae) in citrus orchards for all evaluations.…”
Section: Spatial Distribution Of O Inviraesupporting
confidence: 81%
“…These authors concluded that almost 100% of the variable obtained better adaptation to the spherical model, in comparison to the other models tested. A similar result was also found by Carvalho et al (2015). These authors found that the spherical model was the one that better adjusted the infestation of Gymnandrosoma aurantiana larvae (Lima, 1927) (Lepidoptera: Tortricidae) in citrus orchards for all evaluations.…”
Section: Spatial Distribution Of O Inviraesupporting
confidence: 81%
“…In the case of leaf-cutting ants Atta spp., the dominant influence of some soil characteristics (aeration and humidity, for example) favor the development and survival of the ant's colony, which results in the nest's aggregation. Carvalho et al (2015) report that fruits attacked by G. aurantiana are distributed in aggregate form in the citrus orchard, as observed for M. hemipterus in oil palm Elaeis guineensis plantation (Dionisio et al, 2015).…”
Section: Resultsmentioning
confidence: 75%
“…The PNE was also observed in other insect species, Atta spp. (Hymenoptera: Formicidae) in Eucalyptus forest (Lasmar et al, 2012), Gymnandrosoma aurantiana (Lima, 1927) (Lepidoptera: Tortricidae) in the citrus orchard (Carvalho et al, 2015) and Metamasius hemipterus (Coleoptera: Curculionidae) in oil palm field (Dionisio et al, 2015). In the case of leaf-cutting ants Atta spp., the dominant influence of some soil characteristics (aeration and humidity, for example) favor the development and survival of the ant's colony, which results in the nest's aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty phytophagous insects have been identified that feed on pecan plants, 3 of which are common in North America where this species is indigenous: Phylloxera devastatrix Pergande and Phylloxera notabilis Pergande (both Hemiptera: Phylloxeridae), and Gymnandrosoma aurantiana is known in Brazil as the citrus fruit borer, and became a key pest by the end of the 1980s, when larval injuries on fruits became serious damage, and compromised the use of fruits for industry or for consumption in natura, resulting in loss of production up to 50% (Prates 1992;Parra et al 2004;Carvalho et al 2015). This led to research efforts aimed at lowering losses, and basic studies on biology, rearing techniques, monitoring, and use of egg parasitoids, which resulted in parameters for G. aurantiana pest management, particularly in the state of São Paulo, the largest citrus producer in Brazil (Garcia & Parra 1999;Vilela et al 2001;Parra et al 2004;Bento et al 2006;Molina & Parra 2006).…”
Section: First Report Of Gymnandrosoma Aurantianum (Lepidoptera: Tortmentioning
confidence: 99%